To build a fire and other stories - London, Jack; Kane, Annette P. (Washington, D.C. : Office of English Language Programs, 2005)
Jack London's To build a fire and other stories is one ofe the famous stories of survival in the wilderness. Included in this collecction are stories of the yukon and Alaska from 100 years ago filled with colorful characters and adventures that show London's love of life, of people and adventure.
CONTENTS The wanderer of the north The law of life To the man on trail Love of life To build a fire The wit of porportuk Glossary
Incluye Contents
Incluye Glossary
Keywords: ENGLISH LITERATURE; SHORT STORIES